(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The main idea of this article is the need to actively involve the family in the process of resolving pedagogical conflicts that arise at the initial stage of education. Collaboration with parents allows you to create a stable alliance, which has a positive effect on the educational process and atmosphere in the classroom. Interaction between the teacher and the family system contributes to a better understanding of the interests and needs of children, which in turn helps to minimize emerging disagreements